Memahami Makna Panggilan Abraham Dalam Konteks Pendidikan Agama Kristen - Jenius Harita (Jurnal Pendidikan Agama dan Teologi, 2023)
The meaning of Abraham's call for Christian Religious Education is important in practicing Christian teachings today. By understanding Abraham's calling, Christian teachers can apply the steps that Abraham used during his life to the teaching of Christianity. The research method used is qualitative through analysis of scriptural texts and related literature. The values contained in the history of Abraham's call, such as faith, patience, obedience, and submission are very relevant to Christian religious education. This paper also discusses how to apply these values in the context of Christian education, including reflective and interactive learning. However, understanding the meaning of Abraham's call in the context of Christian religious education presents challenges, including differences in interpretation and understanding that arise from different Christian traditions. The solution to this challenge is to increase insight and understanding through dialogue between Christian traditions and interfaith studies. This paper also provides solutions to overcome challenges in understanding the meaning of Abraham's call, and the need for greater insight and understanding through dialog between Christian traditions and interfaith studies.